ApoE [−/−] CA1-overexpressing knock-in mice aggravated atherosclerosis by increasing M1 macrophages - Jinbao Zong; Changyuan Wang; Hongji Zhou; Yu Song; Kehua Fang; Xiaotian Chang (Atherosclerosis Plus)
Background: Carbonic anhydrase I (CA1) has been reported to be a diagnostic and therapeutic target for atherosclerosis (AS). This study aimed to verify the essential role of CA1 in AS progression in CA1-overexpressing mice. Methods: A ApoE [−/−] CA1-overexpressing knock-in mouse model was constructed via CRISPR/Cas9-mediated genome engineering. AS was then induced in these transgenic mice via the administration of a high-fat diet, and a second group simultaneously received treatment with methazolamide (MTZ), a carbonic anhydrase inhibitor. Results: Compared with ApoE [−/−] mice without CA1 overexpression, CA1-overexpressing mice had a greater average body weight, regardless of whether their treatment with MTZ or their AS induction status. Sudan IV, hematoxylin and eosin and Oil Red O staining revealed more plaques and fat deposits in the cardiac aortas of CA1-overexpressing mice than in those of ordinary ApoE−/− mice when AS was induced. Moreover, the atherogenic index; low-density lipoprotein, total cholesterol and triglyceride levels were significantly elevated, and high-density lipoprotein levels were declined in the peripheral blood of CA1-overexpressing mice than in that of ordinary ApoE [−/−] mice, regardless of whether these animals were induced to AS. Immunohistochemistry, Von Kossa staining and fluorescence immunohistochemistry revealed increases in CA1 expression, calcium deposition and M1 macrophages in the aortic tissues of CA1-overexpressing mice with AS. MTZ treatment significantly suppressed AS pathologies in the above experiments. Conclusion: These findings revealed aggravated AS in ApoE [−/−] CA1-overexpressing mice and suggest that CA1 aggravates AS by increasing M1-type macrophages, a proinflammatory macrophage subtype.